Need for National Standards in Transportation System Information, Acquisition, Processing, and Sharing. Issue 1 (January 2015) - Mobarak, Richard; Albright, David
New methods of transportation system monitoring encourage revisiting current standards and establishing new standards. This paper demonstrates the need for national standards for monitoring roadway motorized and nonmotorized transportation on the basis of the experience of a local government. Three demonstration projects are presented; they were initiated between 2007 and 2013 by Bernalillo County, New Mexico. An adaptive traffic control demonstration project presents the need for standards for video monitoring of roadway traffic volume. A speed monitoring network pilot project presents the need for standards for Bluetooth and crowdsource vehicle speed and travel times. A regional bicycle monitoring demonstration project presents the need for standards for bicycle and pedestrian counts with the use of video monitoring, infrared detectors, inductive loops, and other technologies. Needed standards for transportation system monitoring include data acquisition to ensure that data definitions are consistent and data acquired are comparable. Needed data processing standards include consistent identification and treatment of errors and calculation of summary statistics. Needed data sharing standards include ability to share and combine separate data sets and expand data use. Standard-based roadway motorized and nonmotorized transportation system data, at all levels of government and the private sector, have the potential to improve current practice and public service. Standards have been and remain vital to the transportation profession. This paper recommends new transportation system standards based on the involvement of and cooperation among governmental agencies, the private sector, and standards-setting organizations.